Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1177/004051750007000611
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ozone as an Air Pollutant on Polypropylene Fiber Properties

Abstract: Ever increasing ozone concentrations in the earth's atmosphere polluted by photochemical smog raise the question of possible ageing of fibers in such an environment. This paper investigates polypropylene fibers characterized by pronounced ageing in the natural environment under the impact of sunlight. Fibers are exposed to ozone for varying times and temperatures in a concentration range that can be expected in a heavily polluted urban industrial environment. Changes in the level of chemical composition and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Appearance of a band in 1708 cm -1 , region of ketone carboxyl groups (C=O), also reflects changes occurring in the polymer structure. Although Cataldo 12 had observed that materials with single bonds showed great resistance to ozone attack, in the present work two polymeric materials, PP and PDMS, have suffered break of the single bonds due to ozone attack at high concentrations used, as observed in the literature [13][14][15] . Similar modifications were also observed for PDMS membranes (Figure 5b), moreover for prolonged exposition to ozone it was observed changes in the spectral region 2990-2855 cm -1 and 1485-1415 cm -1 of alkyl groups (-CH 3 ) from long chain with stretching vibration (symmetric and asymmetric) and asymmetric bending vibration, respectively 32 .…”
Section: Infrared Analysis Of the Polymersmentioning
confidence: 51%
See 1 more Smart Citation
“…Appearance of a band in 1708 cm -1 , region of ketone carboxyl groups (C=O), also reflects changes occurring in the polymer structure. Although Cataldo 12 had observed that materials with single bonds showed great resistance to ozone attack, in the present work two polymeric materials, PP and PDMS, have suffered break of the single bonds due to ozone attack at high concentrations used, as observed in the literature [13][14][15] . Similar modifications were also observed for PDMS membranes (Figure 5b), moreover for prolonged exposition to ozone it was observed changes in the spectral region 2990-2855 cm -1 and 1485-1415 cm -1 of alkyl groups (-CH 3 ) from long chain with stretching vibration (symmetric and asymmetric) and asymmetric bending vibration, respectively 32 .…”
Section: Infrared Analysis Of the Polymersmentioning
confidence: 51%
“…Nevertheless, some authors proposed a simple mechanism of initiation and propagation for ozone attack of single bonds structures where various groups, as carboxyl, ketone, etc., are created with elevated ozone concentrations [13][14][15] . Goto et al 16 evaluated the chemical reactivity between ozone and different polymers through material thickness reduction.…”
Section: Introductionmentioning
confidence: 99%
“…It is also essential to know that the higher the energy of the UVR, the greater the degradation will be since it will more easily break the chemical bonds of the textile fibers [189]. These modifications are not immediately observable but develop over time, dependent on the radiation exposure conditions [189,191].…”
Section: Issues About the Effect Of Light Radiations On The Textile O...mentioning
confidence: 99%
“…Although the continuous melt-spinning process was used to prepare the PTFE fiber, the fiber showed low mechanical strength compared to typical polymerbased fibers, such as polyethylene terephthalate (PET), polyamide (PA6), and polypropylene (PP). [29][30][31][32] We therefore tried the post-thermal drawing process to not only reduce density but also enhance orientation of the polymer chain, resulting in increased crystallinity and mechanical strength. The thermal drawing was conducted in the stretching zone (between rollers 3 and 4, see Figure 3(a)) at 155 C. We defined the thermal drawing ratio of the PTFE fibers from the speed of the fast (4)/slow (3) roller.…”
Section: Post-thermal Drawing Process Of Ptfe Fibermentioning
confidence: 99%